Correlation between Placenta Accreta and History of Cesarean Section among Iraqi Pregnant Women: Retrospective study - Abdulla, Nour Ali; Ghafel, Hawraa Hussein (Journal of Contemporary Medical Sciences, 2021)
Objectives: To Identify demographic characteristics of pregnant women with placenta accreta and to find out the correlation between placenta accreta and history of C/S. Methods: A retrospective study was conducted at Maternity wards in Baghdad City's. The study sample consists of (410) pregnant women diagnosed with placenta accreta who undergo a cesarean section. Retrospective study for last three years ago ( January /2018 to December/ 2020). The data collected from patient records in the Statistical Department of the maternity hospitals. Result: The findings of the study shows that a highly significant relationship between placenta accreta and history of cesarean section among pregnant women as indicated by a strong positive correlation at p-value= 0.001. Conclusion: There is a correlation between placenta accreta and history of cesarean section among Iraqi pregnant women.